Draft genome and description of Aeromicrobium phoceense strain Marseille-Q0843T sp. nov., a new bacterium isolated from human healthy skin. (November 2020) - Boxberger, M.; Ben Khedher, M.; Magnien, S.; Cassir, N.; La Scola, B.
Abstract: In 2019, by culturing a skin swab sample from the back of the hand of a 61-year-old healthy woman and assessing it via the culturomics method, we isolated the new bacterial strain Marseille-Q0843 T (= CSUR-Q0843). Matrix-assisted desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) failed to identify this isolate. Analysis of the 16S ribosomal RNA gene and genome-to-genome comparison suggested that this taxon belongs to a novel bacterial species within the family in Nocardioidaceae in the phylum Actinobacteria . We describe here the main phenotypic characteristics, genome sequence and annotation of Aeromicrobium phoceense strain Marseille-Q0843 T, a new member of the Aeromicrobium genus, which we propose as the type strain.